Pengaruh Pertumbuhan Laba dan Struktur Modal Terhadap Kualitas Laba Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2021 - Eldi; Nurwahandiah, Al Ismi (Insan Cita Bongaya Research Journal, 2023)
This study aims to determine and analyze the effect of profit growth and capital structure on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange in 2020 - 2021. Data collection uses secondary data obtained from financial reports accessed via www.idx.co. id. The population in this study are manufacturing companies that are listed on the Indonesia Stock Exchange in 2020-2021 with a total of 193 companies. Determination of the sample in this study using purposive sampling technique. The sample used in this research is 99 manufacturing companies. the method used to analyze the data is multiple linear regression analysis using the SPSS (Statistical Product and Service Solution) version 26 program. The results showed that earnings growth had a positive and significant effect on earnings quality, and capital structure had a positive and significant effect on earnings quality